Human Capital Development in Developing Countries: A Comparative Bibliometric Analysis - Judijanto, Loso; Wahdah, Ghoriqna Fibahril; Ibrahim, Ely; Syamsinah, Syamsinah; Rizal, Rizal (Westscience Press, 2025)
This study presents a bibliometric analysis of research on human capital development in developing countries, utilizing data from the Scopus database and visualization tools from VOSviewer. By examining 1,842 scholarly publications from 2000 to 2024, the analysis identifies key themes, influential authors, collaboration patterns, and temporal trends in the literature. The findings highlight that “human capital” is closely interlinked with core concepts such as “economic development,” “education,” and “sustainable development,” reflecting its central role in the discourse on inclusive growth. Over time, research has expanded to encompass newer topics like “innovation,” “climate change,” and “foreign direct investment,” indicating a shift toward integrative and forward-looking frameworks. Co-authorship and country collaboration maps reveal a dominant role of developed nations, particularly the United States, but also an encouraging rise in contributions from emerging economies in Africa and Asia. While the literature is increasingly diversified and collaborative, gaps remain in gendered analysis, informal labor perspectives, and South–South knowledge production. This study underscores the need for more inclusive, interdisciplinary, and context-sensitive approaches to advance the human capital agenda in developing countries.